2019
DOI: 10.1097/pgp.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Immunomodulatory Molecules PD-1, PD-L1, and PD-L2, and their Relationship With Clinicopathologic Characteristics in Endometrial Cancer

Abstract: Chemotherapeutic agents are not very effective in treating advanced endometrial cancers (ECs). Recent studies have demonstrated the immune evasion mechanism of tumors and possible remedies. Programmed cell death protein 1 (PD-1), programmed death ligand 1 (PD-L1), and programmed death ligand 2 (PD-L2) are immunomodulator molecules that have been the focus of research in lung cancer, melanoma, and renal cell cancer. However, there are few studies concerning EC. This retrospective study aimed to determine PD-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…PD-L1 expression has been shown to be a prognostic marker of prognosis in various cancers, including lung cancer, esophageal squamous cell carcinoma, pancreatic cancer, and colorectal cancer (5)(6)(7)(8). Many studies have also explored the prognostic value of PD-L1 in EC, with conflicting results (9)(10)(11)(12)(13)(14)(15)(16)(17). Some investigators have reported that elevated PD-L1 expression is associated with shorter survival (16).…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 expression has been shown to be a prognostic marker of prognosis in various cancers, including lung cancer, esophageal squamous cell carcinoma, pancreatic cancer, and colorectal cancer (5)(6)(7)(8). Many studies have also explored the prognostic value of PD-L1 in EC, with conflicting results (9)(10)(11)(12)(13)(14)(15)(16)(17). Some investigators have reported that elevated PD-L1 expression is associated with shorter survival (16).…”
Section: Introductionmentioning
confidence: 99%
“…PD-L2 expression was evaluated in type II ECs in 12 patients and 7 (58,3%) were positive for PD-L2 without a significant difference among patients with different ages, differentiation status, clinical stages, histological types, or status of vascular invasion in the tumor (23). Additionally, as reported by Sung and collaborators, analyzing 127 EC tumor specimens (113 classified as type I), PD-L2 expression seems to differ from PD-L1 with PD-L1 positive staining in tumor cells at 36.2% and 64.4% with PD-L2 (24). In previous works, no significant differences in PD-L2 expression have been found between normal endometrium and type I tumor (23,25,26).…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, 14.3% of healthy endometrial tissues and 17.3% of EA tissues were positive for PD-L1 expression, while 20.0% of healthy endometrial tissues and 37.3% of EA tissues were positive for PD-L2 expression [88]. Sungu et al found positive staining for PD-L1 (36%), PD-L2 (64.4%), and PD-1 expression (61.6%) in EA cells, and positive PD-L1 (36.2%) and PD-L2 (93.2%) expression in immune cells [89]. Collectively, the findings show that the synergism between PD-1, PD-L1, and PD-L2 could be a possible target for immunotherapy in advanced EA.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%